NUTRITIONAL AND LIFESTYLE DETERMINANTS IN THE PATHOGENESIS AND PROGRESSION OF AGE-RELATED MACULAR DEGENERATION - Piotr Kupidłowski; Julia Ciechanowicz; Stanisław Ciechanowicz; Julia Dura; Marika Gutowska; Agata Nowacka; Adrianna Perzanowska; Aleksandra Przybylska; Zuzanna Tomaszewska; Anna Zielińska (International Journal of Innovative Technologies in Social Science, 2025)
Age-related macular degeneration (AMD) is a leading cause of irreversible vision loss among the elderly, with its global prevalence expected to rise substantially in the coming decades. Given its multifactorial pathogenesis—driven by oxidative stress, retinal pigment epithelium (RPE) dysfunction, and chronic inflammation—identifying modifiable nutritional and lifestyle risk factors has become a central focus in developing preventive strategies. This review article synthesizes current literature retrieved from PubMed and Google Scholar to examine the influence of dietary fatty acids, antioxidants, smoking, and alcohol consumption on the onset and progression of AMD. Key sources include large-scale observational cohorts and randomized controlled trials, notably AREDS and AREDS2. Long-chain omega-3 polyunsaturated fatty acids (PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), primarily obtained from fish, show consistent protective effects against both early and late AMD. In contrast, excessive omega-6 intake and an unfavorable omega-6 to omega-3 ratio may promote retinal inflammation. Antioxidants and zinc significantly reduce the risk of disease progression, particularly in individuals with intermediate AMD. Lutein and zeaxanthin offer additional benefits. Smoking is one of the strongest modifiable risk factors, with persistent effects even after cessation. Moderate to heavy alcohol consumption correlates with early-stage AMD. Robust evidence supports the implementation of public health strategies focused on smoking cessation, reducing alcohol intake, and promoting nutrient-rich diets to lower AMD incidence and progression. Integrating nutritional counseling into routine ophthalmologic care represents a biologically plausible and cost-effective approach to preserving vision and improving long-term outcomes in at-risk populations.